O processo de escrita da carta pessoal por estudantes da educação de jovens e adultos - Ramalho, Lindolfo Santos (2016)
This study dealt with the process of writing a personal letter by students of Youth and Adult’s Education program. Its main goal was to understand how the Portuguese Language teacher can contribute to the improvement of the writing process in the Youth and Adult’s Education, by writing a personal letter. These were the specific goals of this study: to identify and analyze the main difficulties presented by students of Youth and Adult’s Education program when writing a personal letter; to enable the student of the Youth and Adult’s Education program the understanding that the improvement of their writing will be relevant throughout their personal and professional lives; to evelop a writing strategy which can be applied in the classroom, aiming at a facilitator path between teacher and student in the process of writing a personal letter. The theoretical references were constituted by three axes: Youth and Adult’s Education program, Textual Genres and the personal letter based on authors such as Antunes (2009), Arroyo (2011), Cavalcante (2013), Creswell (2007), Demo (2008), Dolz, Noverraz and Schneuwly (2004), Ferraro (2009), Franco (2005), Freire (1993), Lüdke (1986), Marcuschi (2002, 2008, 2010), Oliveira (2014), Paiva (2015), Schneuwly (1994) and Vieira (2009), and also on papers such as the Portuguese National Teachers' Guide (1997/98/01) and the Law on Guidelines and Bases of National Education (9,394 / 96). As for its methodology, the research was structured in a qualitative approach, through a field study: the participant research, using instruments or collecting data, such as: the participant observation, the conversation wheel and the questionnaire. Data analysis took place through content analysis. Five students from the Youth and Adult’s education program took part in the study: 4 female and 1 male, all of them from the second segment, of a municipal school of Primary Education in Mamanguape-PB. After the theoretical constructions and the methodological path of the research, we presented the analysis of the productions of a personal letter, as well as the texture between the goals and the data collected in the research. The results of the analysis indicated that the written production of a personal letter, developed through a didactic sequence created by Dolz, Noverraz and Schneuwly (2004), enabled the participants of the research to acquire linguistic-discursive knowledge that is necessary for the construction of the genre personal letter, as well as helped them recognize and at the same time overcome the main difficulties they presented during the process of writing a personal letter. Finally, I present as a suggestion to teachers the systematization of a possibility of working with the personal letter in the Youth and Adult’s education program.